Azathioprine is effective for oral involvement in Crohn's disease but not for orofacial granulomatosis alone. (23rd November 2015) - Mentzer, A.; Goel, R.; Elliott, T.; Campbell, H.; Hullah, E.; Patel, P.; Challacombe, S.; Escudier, M.; Sanderson, J. D.
Abstract : Background: There have been no previous reports assessing the effectiveness of azathioprine (AZA) in the treatment of orofacial granulomatosis (OFG). This report is a review of patients receiving AZA for active OFG with or without concomitant gut Crohn's disease (CD) in a specialist tertiary referral centre. Methods: Clinical response was defined by Global Physician Assessment at 4‐, 12‐ and 24‐month follow‐up and a standardised oral disease activity score (ODAS). Results: Sixty of 215 patients seen with OFG in our clinic over a 12‐year period were treated with AZA. Of these, 22 had concomitant CD. The proportion of patients responding to AZA with a diagnosis of CD/OFG vs. OFG only at 4, 12 and 24 months were 54% vs. 21% ( P = 0.03), 59% vs. 21% ( P = 0.003) and 41% vs. 24% ( P = 0.16), respectively. A statistically significant difference was seen between starting and follow‐up ODAS scores at 4 months in the CD/OFG group which was not observed in the OFG only group. Factors predicting a need for AZA included a diagnosis of intestinal CD, sulcal swelling, sulcal ulcers and upper lip involvement. The factor predicting response to treatment was a diagnosis of CD at 12 months of follow‐up. No difference in the number of adverse effects was observed between the two groups of patients. Conclusions: AZA is significantly more effective in the treatment of oral disease with a concurrent diagnosis of CD rather than in the treatment of OFG alone.